Optimization of chitosan concentration on physicochemical properties of polyvinyl alcohol-based hydrogel - Muhammad Saupi, Azuri; Forid, Md Shaekh; Wan Maznah, Wan Ishak; Nurul Ain Athirah, Azhar (International Scientific Organization, 2023)
Hydrogels are an interconnected three-dimensional polymeric network that are widely applicable for drug delivery, wound healing, tissue engineering and other biomedical uses. Recently, chitosan/polyvinyl alcohol hydrogels have been investigated for use as drug delivery carriers due to their ability to encapsulate, carry and release the drug to the intended target.. For this purpose, the study was designed to fabricate a chitosan/ polyvinyl alcohol hydrogel and optimize the chitosan concentration in the hydrogel. To fabricate the chitosan/ polyvinyl alcohol hydrogel, chitosan at concentrations of 1.5%, 2.0%, 2.5%, and 3.0% were used and the polyvinyl alcohol concentration was fixed at 2.0% for each formulation. The chitosan/ polyvinyl alcohol hydrogels were investigated on their physicochemical properties, which were swelling rate, water vapour transmission rate, porosity and mechanical properties including tensile strength and elongation at break. Furthermore, the prepared hydrogels were characterized for functional properties using fourier-transform infrared spectroscopy and scanning electron microscope. The results showed that 1.5% chitosan/ polyvinyl alcohol hydrogel had the best physicochemical properties among the tested formulations. FTIR results for all formulations meet the criteria. The surface morphology of 1.5% chitosan/ polyvinyl alcohol hydrogel showed a porous structure. The results suggest that 1.5% chitosan/ polyvinyl alcohol hydrogel could be suitable for biomedical and pharmaceutical applications